Diversity of coronaviruses in wild and domestic birds in Vietnam - Vasily Y Marchenko; Natalia P Kolosova; Alexey V Danilenko; Maria K Bragina; Tran Thi Nhai; Alexander B Ryzhikov (Asian Pacific Journal of Tropical Medicine, 2022)
Objective: To investigate the genetic diversity of coronaviruses in wild and domestic birds in the bird park and live poultry markets of Ca Mau province in Vietnam in 2020. Methods: A total of 228 samples (121 from wild birds and 107 from poultry) were collected in the territory of Ca Mau province of Vietnam in 2020. The avian samples were tested for the presence of the four genera of coronaviruses using reverse transcription and nested PCR. Molecular genetic analysis using targeted NGS sequencing of RdRp gene was performed for 29 representative samples (12 samples from wild birds and 17 from poultry). Phylogenetic analysis was performed using the neighbour joininig method with 1000 bootstrap replications using MEGA X software. Results: Among wild birds, 21.5% samples were positive for the genetic material of coronaviruses and 38.3% samples were positive for coronaviruses among poultry. Genetic analysis of the partial sequence of RdRp gene from representative samples revealed that wild birds were carriers of gammacoronaviruses and deltacoronaviruses. Among poultry, three genotypes of infectious bronchitis virus (QX, Mass and Q1) were detected in chickens, with QX genotypes being predominant, and viruses of DCoV group were detected in domestic ducks. There was no detection of alphacoronaviruses or betacoronaviruses in the studied birds. Conclusions: Coronaviruses of genera Gammacoronavirus and Deltacoronavirus were detected in wild birds. A high percentage of infectious bronchitis virus was detected in poultry. Thus, there is a need for broader surveillance of coronaviruses in birds, which can be used for evaluation of diversity, evolution and distribution of coronaviruses in Vietnam. Continuous surveillance of coronaviruses circulation in wild and domestic animals is necessary for implementing strategic measures for poultry and domestic animal protection and for evaluation of possible risk of circulating coronaviruses to human health.